Demographic situation in Russia: the present and the future - S. V. Soboleva; N. E. Smirnova; O. V. Chudaeva (Мир новой экономики, 2018)
In the article the changes of demographic situation are analysed for the period 1980-2013 in Russia. On the basis of the statistical accounts data of Rosstat for more than 30-years period the dynamics of basic constituents of population reproduction is presented. It is shown as their changes had influence on the forming of the present and the future age and sex structure. An important feature of the modern period is a decrease in the absolute and relative number of working-age population and the ageing of this cohort, significantly reduces the employment potential and making very problematic the implementation of optimistic scenario of economic growth. It is noted that despite the undoubted successes of Russia in the demographic sphere in recent years, the output from depopulation can be short-term due to the nature of the existing age structure and negative changes of the demographic potential in the past. To avoid further depopulation resume with renewed vigor demographic mobilization is necessary for Russia, in which the principal target for demographic policy should become a family with 3-4 children. Exactly such a family should acquire the largest economic and moral support from the state and society.